Intravitreal Bevacizumab (Avastin) as an Adjuvant for the Treatment of Posterior Scleritis - Lim, Ji Won (The Korean Ophthalmological Society, 2011)
We report a case of posterior scleritis effectively managed with intravitreal bevacizumab. A 71-year-old woman was diagnosed with posterior scleritis. Although she was initially treated with systemic steroids, her clinical presentation deteriorated. She was then treated with a single intravitreal injection of bevacizumab and aqueous humor collection. The aqueous level of vascular endothelial growth factor prior to the intravitreal injection was 880.51 pg/mL, greater than that in the healthy control group (p < 0.001). One month later, the scleritis was completely resolved, and the patient remained stable during six months of follow-up. Intravitreal bevacizumab appears to be an effective adjuvant therapy for patients with posterior scleritis.